Fabricating a simple fan system for small low speed wind tunnel and studying the parameter for frequency adjustment - Nur Hidayah, Hashim (2012)
Wind tunnel fan frequently come without control box or instrument especially for axial fan that widely sell in the market. This may lead to unfavourable condition which the fan speed could not be remote. We may severally found the fan that could be control by some fix parameter option such as velocity and we only could use that certain speed for testing. The speed of motor also could not be increase. In this research, fabrication of fan system of small low speed wind tunnel that can control speed by varying the frequency was performed. The connection used three phase of Miniature Circuit Breaker, AC inverter and fan motor. AC inverter was installed for controlling the frequency of motor. This AC inverter could remote the frequency according to user mode and could increase the frequency of the motor. The legs and base for the fan were added for attachment to horizontal wind tunnel. An experiment of varying the frequency to get the pressure in the test section was done. Graph was plotted, which is pressure versus frequency. An analysis was done based on the graph. Starting that point, the velocity was calculated in order to plot graph of velocity versus frequency. The relationship of the parameters was established. From this experiment, user could know and adjust the frequency according to the pressure and velocity that they desired simply by rotating the knob of the AC inverter.